No Effect of the Dietary Inflammatory Index on Psychological Health During Caloric Restriction: A Secondary Analysis of the CALERIE Trial Data. (29th May 2020) - Silver, Rachel; Roberts, Susan; Naumova, Elena; Chui, Kenneth; Kramer, Arthur; Das, Sai Krupa
Abstract: Objectives: Anti-inflammatory diets have been suggested to improve psychological health. This research evaluated the combined effects of consuming an anti-inflammatory diet and caloric restriction (CR) on changes in perceived stress and health-related quality of life in a healthy, non-obese population. Methods: We conducted a secondary analysis of the publicly available CALERIE data. Participants were randomized to a 2 year CR intervention (n = 143) or an ad libitum Control group (n = 75) and self-selected their dietary intake. An energy-adjusted dietary inflammatory index (DII) was calculated based on 28 components from self-reported food records. Self-reported stress and general health outcomes were measured using validated questionnaires. Linear mixed models were used to assess changes in each outcome from baseline to 12 and 24 months. Models were adjusted for age, sex, baseline outcome measure, change in body fat, and a treatment by DII interaction term. Results: On average, participants were 38.1 ± 7.2 years old with a BMI of 25.1 ± 1.7 kg/m 2 . Baseline characteristics, including the DII, stress, and general health, did not differ with randomization. There was no significant association between temporal changes in DII and changes in stress or general health in the CR or Control groups. On average, both groups tended to report higher stress at 12 months; however, there was no difference in perceived stress between groups (adjusted mean difference [MD]: 0.5; 95% confidence interval [CI]: −0.4, 1.5; P  = 0.25). There was an improvement in reported general health in the CR group at 12 months (MD: 4.1; 95% CI: 2.2, 6.0; P  < 0.001), but not in Controls (MD: 1.6; 95% CI: −1.2, 4.3; P  = 0.26). Yet self-reported general health was similar both groups (MD: 2.5; 95% CI: −1.3, 6.3; P  = 0.16). The effect of a CR intervention on both outcomes did not differ with change in DII. Similar results were observed at 24 months. Conclusions: There was no indication of any contribution of a low DII score on perceived stress and general health in the presence of CR. Additional research is required to enhance our understanding of the implications of dietary inflammation on a broad range of psychological health outcomes. Funding Sources: Jean Mayer USDA Human Nutrition Research Center on Aging Doctoral Scholarship; USDA agreement #8050–51, 000-105–01S.